2014
DOI: 10.2304/elea.2014.11.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Polysynchronous: Dialogic Construction of Time in Online Learning

Abstract: Online learning has been conceptualized for decades as being delivered in one of two modes: synchronous or asynchronous. Technological determinism falls short in describing the role that the individuals' psychological, social and pedagogical factors play in their perception, experience and understanding of time online. This article explores the history of synchronous and asynchronous concepts and argues that an examination of students' perception of time in online contexts is required if we are to move past as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…First, the flexibility of the course entails an easy navigation within the platform and thoughtful allotments of time according to study activities, in a way that keeps students in the same pace with the organizational time and space as designed by the course. The discussion board activities, which are also the topic of concern of Khoo and Cowie (2014) and Oztok et al (2014), a.o., can as well contribute to building productive learning relationships. More broadly speaking, flexibility should involve granting access to a variety of facilities and activities available on campus to students taking the course online.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the flexibility of the course entails an easy navigation within the platform and thoughtful allotments of time according to study activities, in a way that keeps students in the same pace with the organizational time and space as designed by the course. The discussion board activities, which are also the topic of concern of Khoo and Cowie (2014) and Oztok et al (2014), a.o., can as well contribute to building productive learning relationships. More broadly speaking, flexibility should involve granting access to a variety of facilities and activities available on campus to students taking the course online.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent attempts to bring more nuances to the notion of time, several researchers have paid closer attention to the learners' experience regarding time. For example, Kabat (2014) and Oztok et al (2014) have challenged the conventional dichotomy of time as being synchronous and asynchronous. By investigating the students' discussion board, Oztok et al (2014) found that there the time is displayed to the students both linearly and non-linearly.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These include synchronous experience, asynchronous modes of study (e.g. Chiero and Beare, 2010;Olson and Werhan, 2005) and indeed, a blurring of current binaries of synchronicity and asynchronicity, such that traditional notions and understanding of 'time' become redundant (Dalgarno, 2014;Oztok, et al, 2014). These variants are likely to proliferate in the future as learners demand a more customised form of higher education.…”
Section: Changing Knowledge Demands Changing Technologymentioning
confidence: 99%
“…Within CSCL environments where engaging in discussion about course materials is the primary focus for students, text-based exchanges provide the learner with an opportunity to produce coherent contributions to the discussion as there is more time to gather thoughts (Solan & Linardopoulos, 2011, p. 453) than in a face-to-face, synchronous setting. In general, time is seen to expand in online discussions, as students can participate when they choose (Oztok et al, 2014). One worry is that this constant course availability may be draining, although many students are willing to spend extra time for the benefits inherent in reading well-reasoned messages (Meyer, 2003).…”
Section: Practitioner Notesmentioning
confidence: 99%